A comparison of the performance of high-voltage insulator materials in a severely polluted coastal environment - Vosloo, Wallace L. (Wallace Lockwood) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2002.